Moisture Migration and Control of New Embankment for Reconstruction and Expansion Project in Southern China - Junhui Zhang; Feng Li; Ling Zeng; Junhui Peng; Le Ding; Liang He (Advances in Civil Engineering)
In hot and humid regions of southern China, the volumetric moisture content of the embankment after opening to traffic for a period of time reaches a stable state, and it is higher than the design value. When it was widened, the humidity gradient and exchange were formed due to the difference in moisture content between the existing and new embankment. To reveal the moisture migration of the existing and new embankment and control the rise of volumetric moisture content in new embankment, six frequency domain reflectometry sensors were installed in existing and new embankment to monitor the volumetric moisture content. A finite element model for the embankment was established and verified with the measured data. And seven numerical analyses of transient seepage in the new embankment of the cushion, cover, and partition using capillary barrier by sand were simulated. The results show that the volumetric moisture contents of the new embankment in southern China gradually increase and eventually reach an equilibrium state. The increase in water comes from the slope, the foundation, and the existing embankment. Early in the first 1∼2 years, the water mainly comes from the foundation and the existing embankment. After that, as time goes by, the water comes mostly from the slope infiltration and gradually migrates to the foundation and the existing embankment. Finally, the volumetric moisture content and the water storage gradually reach equilibrium. The volumetric moisture content of the new embankment using capillary barrier by sand at the cushion, the cover, and the partition is maintained as the construction volumetric moisture content. This combination is a very effective method to control the humidity stability of the new embankment in southern China.